RUANG KREATIFITAS PADA PEMBUATAN TAS BELANJA DENGAN TEKNIK ECO PRINT-POUNDING UNTUK MENDUKUNG BERKELANJUTAN GAYA HIDUP SEDERHANA: KELOMPOK PKK KELURAHAN CIPAGANTI, BANDUNG - Tessa Eka Darmayanti; Christine Claudia Lukman; Wieke Tasman; Wenny Anggraini Natalia; Yunita Setyoningrum; Astrid Austranti Yuwono (Jurnal Abdimas Bina Bangsa, 2024)
Protecting the environment while adopting a simple lifestyle is the commitment of the Empowerment of Family Welfare (PKK) group, Cipaganti Village, Bandung. This issue is also the attention and focus of the team of Community Service lecturers from across the Design Study Program at Maranatha Christian University, Bandung. The plastic shopping waste emergency and the desire to protect the environment are the triggers for the dedicated activity of making shopping bags. Fabric-based bags are more environmentally friendly and aesthetic value is obtained from the eco-print technique that decorates the bag. This technique is a fabric coloring print that uses organic materials in the form of leaves or flowers that contain color pigments and this process does not produce waste that is harmful to the environment. Therefore, the PKK group of Cipaganti Village, Bandung needs assistance from a team of lecturers from the Faculty of Fine Arts and Design, Maranatha Christian University in making shopping bags as an environmentally friendly product to be realized through Community Service (PKM) activities. The product creation process creates an enthusiastic social space while honing the creativity of participants and the Service team